Design and simulation of a mobile robot, for the inspection of electrical lines - Eibar, Carlos; Gavilane, Javier; Pérez, Miguel; Aldás, Édisson; Proaño, Paul; Basantes, David (KnE Engineering, 2018)
Abstract. A mobile robot was designed and simulated for the inspection of electrical lines, which seeks to investigate alternatives that have the main necessary characteristics to perform these inspection tasks and implement them in a robot of accessible costs. In the robot design was modeled its mechanical parts in 3D and then previously taken to a virtual simulation software (Vrep), in which the sequence of movements were programmed, to pass obstacles.